PENERAPAN MODEL TGT PADA MATERI STOIKIOMETRI TERHADAP SISWA KELAS X SMA PGRI 1 PONTIANAK - Firdaus, Muhamad; Hairida, Hairida; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to determine whether there was a significant difference of achievement between students taught using Wondershare Quiz Creator assisted Team Games Tournament and students tought using conventional model and to determine effect of mind toward students achievement. The research design used was nonequivalent control group design. Two class at grade X of SMA PGRI 1 Pontianak participated on this study. Pretest and postest were used to collect data. Analysis to U-Mann Whitney test, the value at Asymp.Sig (2-Tailed) was 0,000. Which meant there was a significant difference with conventional model and Wondershare Quiz Creator assisted Team Games Tournament. Analysis to effect size calculation, the value was 4,21 which confirmed as high. It must the effect of Wondershare Quiz Creator assisted Team Games Tournament (TGT) toward students was high.Keywords: Team Games Tournament, Learning Outcomes, Mole Concept.